A learning model for law enforcement based on the justice value of Pancasila for equitable spatial planning - Kuncorowati, Puji Wulandari; Rachmi Handayani, I Gusti Ayu Ketut; Subekti, Rahayu (Jurnal Cakrawala Pendidikan, 2025)
Approaches in legal education that emphasize the justice value of Pancasila are increasingly relevant in rising environmental awareness among students. A learning model not only offers theoretical insights into environmental protection but also encourages the practical application of justice value in the context of law enforcement. This study seeks to develop a law enforcement learning model based on Pancasila justice value to increase environmental awareness at Yogyakarta State University, Indonesia. The study employed a mixed-methods approach, integrating qualitative and quantitative methods within a research and development (R&D) design. The data were collected using questionnaires, observations, and document analysis. The population consisted of students who took civic education courses at Yogyakarta State University in 2023. A sample was selected using proportionate stratified random sampling, dividing the university's faculties into groups based on cultural similarities, including the Faculty of Social, Legal and Political Sciences; Faculty of Economics and Business; Faculty of Education and Psychology; and Faculty of Languages, Arts and Culture. The results revealed three main findings. First, civic education at Yogyakarta State University required further development in terms of materials, methods, media, resources, and evaluation. Second, developing a law enforcement learning model based on the justice value of Pancasila to increase environmental awareness involved initial, core, and closing activities. These activities included identifying environmental problems, introducing environmental law materials, selecting problems for class research, gathering and documenting information, developing class portfolios, presenting portfolios, and reflecting on the learning experience. Third, the model demonstrated effectiveness and significantly increased student's environmental awareness at Yogyakarta State University, effectively increasing their understanding of theory and practice.